Основы пожарной теплофизики: учебник - Башкирцев М. П. Михаил Прокофьевич; Бубырь Н. Ф. Николай Федорович; Минаев Н. А. Николай Алексеевич; Ончуков Д. Н. Дмитрий Николаевич (Москва, Стройиздат, 1978)
Авт. указаны на обороте тит. л.